Control de maquinaria industrial por métodos topográficos (ING) - Roldán Rodríguez, Julio Roberto (2004)
Under industrial maintenance programs, the industry requires the control of working machinery especially machinery operating 24 hours a day. This is done to determine, before hand possible displacements, torsions, tilts, settlements, misalignment and problems of adjustment. In order to quantify these elements, the surveying methods, applied in a special manner, have shown to be efficient. This was experimented on the control described in this article. The control was applied to the transporting system of ceramic for heating into an Incesa Standard S.A. oven. The control was performed with theodolite and a metric steel-tape for horizontal measurements, and a level for vertical measurements. The results allowed the industrial engineers, to apply corrective actions to the problems detect on the transporting system.